The Effectiveness of Utilizing Nox Android Emulator for Interactive Teaching on Students' Writing Competence and Involvement - Edi Pujo Basuki; Novi Rahmania Aquariza (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Learning English, as outlined in Curriculum 2013, is more directed at mastering the ability to write text-based genres. In this study the author introduces game by utilizing the Android Emulator. The problem of this research is to find out the effectiveness of using the Andoid Emulator tool as an effective interactive learning media on the ability to write and the involvement of students in the learning process of writing. The design of this study is pre-test-post-test group design. After implementing the Game Before Writing Procedure using the Nox Android Emulator, a post-test is performed. The population is high school students SMA Bhayangkari 10 Porong. Research samples were 39 students. The Research Instruments are tests and observation sheet. Data Analysis is using the T Test and descriptive. From data, the mean difference is 12,435. This means that Learning with Game Before Writing Procedure has an influence on the ability of Writing Report.. 80% of students are actively involved in the game. Based on the results of the T Test for the Utilization of the Nox Android Emuator in the implementation of Game Before Writing Learning Procedures, it is effective in improving report writing skills. The fun game encourages student involvement